PENGGUNAAN THE ZMIJEWSKI MODEL, THE ALTMAN MODEL, DAN THE SPRINGATE MODEL SEBAGAI PREDIKTOR DELISTING - Mila Fatmawati (Jurnal Keuangan dan Perbankan, 2012)
The purpose of this study was to investigate empirical evidence that the Zmijewski model, the Altman model, andthe Springate models could be used as a predictor of delisting the company. Object of this study was to remove thelist of companies that trade shares (delisted) in Indonesia Stock Exchange in 2003-2009. As a benchmark forcompanies delisted at the top used companies that were still listed on the Stock Exchange with the same numberand kind of business field. Comparison samples were taken randomly over the same period with the companydelisted. The method of analysis used logic regression. The results found that from the three delisting of predictormodels, only the Zmijewski models that could be used to predict the company delisted in the period of observation,while the Altman model and the Springate models could not be used as predictive models delisting. It is becauseThe Zmijewski model emphasized amounts of debt in predict delisting. The bigger the debt was, it would be moreaccurate in predicting as the companys delisting. Meanwhile, the Altman model and the Springate modelemphasized more on profitability measures. The smaller the profitability was, the more precisely to predictcompanys delisting. Condition of delisting the company that became object of observation company trends wasstill able to get profit, but it had a relative amount of debt.